Epidemiologic features and treatment outcomes of pediatric pulmonary tuberculosis cases - Pınar Etiz; Ali Tanju Altunsu (Cukurova Medical Journal, 2020)
Purpose: We here aimed to examine the epidemiologic features and treatment outcomes of pediatric pulmonary tuberculosis cases who were registered to the Adana Tuberculosis Dispensaries. Materials and Methods: Fifty-six pediatric patients aged 0-18 years with the diagnosis of pulmonary tuberculosis were examined retrospectively in terms of demographic data, clinical characteristics and drug susceptibility test results, as well as treatment outcomes. Data were collected through medical record review. Results: The mean age of the patients was 12.84 ± 5.62 years and 46.4% were female. Nine patients (16%) were aged 0-5 years, 4 (7.1%) were aged 5-10 years, 17 (30.3%) were aged 10-15 years and 26 patients (46.4%) were aged 15-18 years. Fourty-eight children was only pulmonary tuberculosis whereas eight possessed characteristics of both pulmonary and extrapulmonary tuberculosis. The most frequent symptoms were prolonged cough (80.3%) and weight loss (73.2%). Drug susceptibility test was performed only 22 patients. Multidrug resistance was determined in one patient. Among the 56 children for whom treatment outcome was documented, 39 (69.6%) were completed treatment, 16 (28.5%) were cured and 1 (1.7%) had treatment failure. Conclusion: It was observed that the signs and symptoms of our patients were compatible with the literature. The epidemiological characterization of pediatric patients with pulmonary tuberculosis helps to provide a better diagnostic approach in this population.